Effect of oyster mushroom wastes on performance, immune responses and intestinal morphology of broiler chickens - Shila Hasanian Fard; Majid Toghyani; Sayed Ali Tabeidian (International Journal of Recycling of Organic Waste in Agriculture)
Background Mushroom wastes are widely left from mushroom production industries and have been supposed to possess prebiotic, antimicrobial, antifungal and antioxidant properties. Due to difficulties with using antibiotic growth promoters in poultry diet, mushroom wastes seem to be a proper substitute for them. Therefore, present experiment was carried out to investigate the effect of oyster mushroom wastes on performance, immune responses and intestinal morphology of broiler chickens. To conduct the trial, total of 210-day-old broiler chickens (Ross 308) were assigned to 3 dietary treatments and 5 replicates of 14 mixed birds. Subsequently, performance, immunity and intestinal morphology parameters were evaluated throughout the experiment. Results 1 % mushroom wastes inclusion not significantly increased body weight (BW), weight gain (WG) and feed intake (FI) of chickens (P[0.05), while using 2 % of these wastes deteriorated BW and feed conversion ratio (FCR) (P.05). At 28 days of age, villus height and crypt depth of jejunum were significantly increased using both levels of mushroom wastes, however, these indices impaired in ileum with the same mushroom levels (P.05). With the exception of antibody titer against Newcastle disease virus which was compromised using 2 %, other antibody-related parameters were not affected by supplementing 1 % mushroom wastes (P[0.05). The ratio of heterophil to lymphocyte also decreased by the waste inclusion (P.05). Conclusion Mushroom wastes in 1 % inclusion are able to improve some parameters of performance and immunity of broiler chicks. Nonetheless, supplementation in 2 % might compromise the mentioned indices.